Film festivals from European geopolitics to global cinephilia - Valck, Marijke de 1975- (Amsterdam University Press, 2007)
The film festival has come a long way from its relatively humble origins in Venice in 1932 - when nine nations presented twenty-five feature films screened in an open-air cinema where men had to adhere to standards of formal evening attire. Hugely popular events that attract diverse lovers of cinema worldwide, today's most famous film festivals - Cannes, Berlin, Venice, and Rotterdam - continue the story of a phenomenon that began in the midst of geopolitical disputes in war-torn Europe. Film Festivals shows how these festivals turned impediments into advantages and developed a successful global network that addresses issues as diverse as programming and prizes, national legitimation, city marketing, cinephilia, glamour, and audience. Discussing the festival as a media event and looking closer at various festival visitors, this volume also questions whether 'successful' is in fact the appropriate term for understanding developments that could be considered dogmatic in their insistence on framing filmmakers as auteurs and films as belonging to 'new waves.' An essential title for everyone interested in the culture
Title from publisher's bibliographic system (viewed on 15 Jan 2021)
Introduction : film festivals as sites of passage -- 1. Berlin and the spatial reconfiguration of festivals : from European showcases to international film festival circuit -- 2. Cannes and the "alternative" cinema network : bridging the gap between cultural criteria and business demands -- 3. Venice and the value-adding process : the role of mediation, segregation and agenda setting -- 4. Rotterdam and the rise of thematic festivals : from cinephile initiatives to popular events -- Conclusion : Successful or safe? : the strengths and weaknesses of the film festival network
Keywords: Geschichte 1932-2005; Film festivals / Europe; Film festivals; Filmfestspiel; Europa; Hochschulschrift